Uppvärmning av mjölkgård med ved, flis eller havre - Larsson, Terje (2005)
The background for my thesis is the fact that with rising electricity and oil prices it becomes interesting to calculate on alternative heating systems. I have chosen to calculate upon my parents' farm, which today heats the dwelling house with wood. This is very time-consuming work, time which could be spent on other work. The main objective for this study is to compare three different heating systems to decide how they differ considering effort and cost. The result from the calculations was that grain-heating system demanded the least amount of work, but the total cost was a little higher compared to chips heating. Chips heating required half as much work as today's wood heating and had a little lower total costs compared with the corn heating. Which system to choose largely depends on how the own work is valued. If one does not want to get paid for their work, then the cheapest alternative is to complement the existing boiler with a chips system. Another influencing factor is if the farm owns its own woods. The forest has to be managed anyway and from there cheap energy may be extracted instead of being sold for little money.